Relationships among provision of care, health and well-being, and engagement in health promoting activity of older adults who are the primary caregivers for spouses with cancer. - Keizer, Mary C. (University of Ottawa (Canada), 1995)
This exploratory study investigated the relationships among the provision of care, physical and emotional health, and exercise and socialization among spousal caregivers of older adults with cancer. The Pender Health Promotion Model formed the conceptual framework for the study. Face to face interviews were conducted with sixty spousal caregivers of elderly individuals with cancer who were being cared for in their home. Findings indicated that the majority of respondents participated in health promoting activities (exercise and socialization) both prior to and following spouses' diagnosis of cancer. There was, however a decline in participation in all forms of physical exercise inquired about, particularly those requiring absence from the home, following spouses' diagnosis. With respect to socialization, face to face interactions with family, friends and others remained unchanged, however, social outings declined dramatically. Caregivers perceived their overall health to have declined since their spouse's diagnosis of cancer. Caregivers provided a substantial amount of assistance to their spouse in the form of personal and instrumental activities of daily living. This study also examined the strength of the major variables as predictors of participation in health promoting activity as hypothesized by the Pender model. Correlational analysis revealed a significant relationship between engagement in exercise and self rated health. Indeed, the greatest predictor of health-promoting activity was prior levels of participation in exercise and socialization, which is not identified as an important predictor of health-promoting activity in the Pender Health Promotion Model. Consequently, alterations to the Pender Model were proposed. (Abstract shortened by UMI.)
Keywords: Gerontology.